Tumor microenvironment as the "regulator" and "target" for gene therapy. (21st May 2019) - Wu, Jiayan; Chen, Jie; Feng, Yuanji; Tian, Huayu; Chen, Xuesi
Abstract: In this review, we focus on strategies for designing functional nano gene carriers, as well as choosing therapeutic genes targeting the tumor microenvironment. Gene mutations have a great impact on the occurrence of cancer. Thus, gene therapy plays a major role in cancer therapy and has the potential to cure cancer. Well‐designed gene therapy largely relies on effective gene carriers, which can be divided into viral carriers and non‐viral carriers. A gene carrier delivers functional genes to their intracellular target and avoids nucleic acids being degraded by nucleases in the serum. Most conventional cancer gene therapies only target cancer cells and do not appear to be sufficintly efficient to pass clinical trials. Accumulating evidence has shown that extending the therapeutic strategies to the tumor microenvironment, rather than the tumor cell itself, can allow more options for achieving robust anti‐cancer efficiency. In addition, unusual features between tumor microenvironment and normal tissues, such as a lower pH, higher glutathione and reactive oxygen species concentrations, and overexpression of some enzymes, facilitate the design of smart stimuli‐responsive gene carriers regulated by the tumor microenvironment. These carriers interact with nucleic acids and then form stable nanoparticles under physiological conditions. By regulation of the tumor microenvironment, stimuli‐responsive gene carriers are able to change their properties and achieve high gene delivery efficiency. Considering the tumor microenvironment as the "regulator" and "target" when designing gene carriers and choosing therapeutic genes shows significant benefit with respect to improving the accuracy and efficiency of cancer gene therapy.